Pengaruh E-WOM (Electronic Word Of Mouth) dan Harga Produk terhadap Minat Beli Konsumen pada Aplikasi Shopee - Nu’man Robbani; Edita Rachma Kamila (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The development of digital technology has significantly changed consumer behavior in making purchasing decisions, particularly on e-commerce platforms. Two important factors influencing consumers’ purchase intention are Electronic Word of Mouth (E-WOM) and product price. This study aims to analyze the effect of E-WOM and product price on consumers’ purchase intention on the Shopee application. This research employed a quantitative approach using questionnaire-based data collection. A total of 91 respondents who had previously made purchases on Shopee participated in this study. Data analysis was conducted using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) method. The results indicate that Electronic Word of Mouth (E-WOM) has a significant effect on consumers’ purchase intention. In addition, product price also has a significant influence on consumers’ purchase intention. Simultaneously, E-WOM and product price demonstrate a strong contribution in explaining variations in consumers’ purchase intention. The findings of this study are expected to provide practical insights for e-commerce platform managers and sellers in developing effective digital marketing strategies, particularly in managing customer reviews and implementing competitive pricing strategies.